Safety and health practice among workers in municipal solid waste management in Sarawak - Mangkau, Ivy Deirdre (2021)
The current issues of safety and health practice among solid waste management workers to date are less highlighted in our country compare to foreign country. This research is important because it provide important information about occupational problems trends in Malaysia as Concessionaires Company neglected safety and health precaution as in the contract. The push for sustainability solid waste management from the aspect of safety and health thru improvement of contract in between Municipal Council (local authority) and Concessionaires Company hopefully can bring awareness to related parties. The research is conducted to study the issues in safety and health practice among solid waste management workers, and to increase stakeholder and public awareness regarding safety and health issues. This research probed and undertaken to determine occupational problems among municipal solid waste management in the context of physical, health, psychological and social health, analyses the safety and health practice as in the contract and, to develop a framework to achieve sustainable solid waste management in safety and health aspects. The methodology adopted was a hybrid approach (mixed method). Through quantitative approach, a survey instrument constructed for occupational problem among solid waste management workers. Meanwhile, qualitative approach, a semi-structure interview involve two safety officer from Concessionaires Company and one municipal council officer are analyses manually. Five key aspects to improve contract at Local Authority level were formulated namely policy, training, emphasis on PPE, inspection and insurance. Meanwhile, five key categories to improve safety and health at Concessionaires level are formulated namely resources, cultural dimension, working condition and employee safety, communication and training. The novelty gained from this research is to form-up framework to achieve sustainable solid waste management in safety and health aspects which already implemented in two districts. It can serve as a benchmark and guidance in addressing the current safety and health practice in waste industry in our country.